The Awareness and Implementation of MBKM Program as Flexible Learning in Faculty - Wahyuningtyas, Ratri; Isynuwardhana, Deannes; Rismayani, Risris; Gunawan, Indra (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research discussed Merdeka Belajar-Kampus Merdeka (MBKM), an independent learning policy for universities in Indonesia issued by the Minister of Education and Culture in 2020. One highlighted policy was the right to study for students to study outside the study program for three semesters. The research intended to determine awareness and implementation of the MBKM program from students, lecturers, and education staff. The research applied a quantitative-descriptive method with a survey model. The research data and information were collected by distributing and filling out questionnaires at the Online Learning System (SPADA) of the Ministry of Education, Culture, Research, and Technology of Indonesia. The data obtained were then processed through several analytical techniques, namely descriptive statistics using rank order and text processing and analysis. The population in the research consisted of students, lecturers, and educational staff at the Faculty of Economics and Business, Telkom University. The research indicates that the level of knowledge of lecturers, students, and educational staff regarding the MBKM program is relatively high, obtained from various sources of information, including through online/offline channels from the Directorate General of Higher Education. Follow-up that needs to be done as part of continuous improvement is the need for easy access to working groups at the Ministry of Education and Culture and the importance of socializing in terms of rules and technical aspects of MBKM implementation so that activities can run more optimally.